A checklist of the water mites of Turkey (Acari: Hydrachnidia) with description of two new species - Erman, Orhan; Pesic, Vladimir; Esen, Yunus; Ozkan, Muhlis (Magnolia Press, 2010)
A review is given of all species of water mites reported from Turkey, based on published records and original data from recent research. In total, 236 species and subspecies in 52 genera and 23 families have been found. Two species, Atractides (Atractides) anatolicus Pesic, Erman & Esen sp. nov. and Atractides (Atractides) martini Pesic, Erman & Esen sp. nov. are described as new to science. The following species are reported for the first time for Turkey: Atractides inflatipalpis K. Viets, 1950, A. remotus Szalay, 1953 and A. orghidani Motas & Tanasachi, 1960. The following synonyms are established: Hydrovolzia persica Bader & Sepasgozarian, 1979 and H. persica anatolica Oezkan, 1982 = H. cancellata Walter, 1906; Arrenurus (Rhinophoracarus) hazarensis Ozkan & Erman, 1990 = A. abbreviator Berlese, 1888. The characteristics of the water mite fauna in the treated area are briefly outlined.
Keywords: Water mites; new species; biodiversity; Turkey; Asia Minor